Pola Konsumsi Berita dalam Era Digital: Perbandingan Preferensi Generasi Z Terhadap Sumber Berita Tradisional dan Modern - Deti, Wilda Okta Dwina; Matondang, Muhammad Alfikri (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
People interaction has changed along with internet development. Digital news (internet-based) is beginning to alter classical ones. The development of social media and other digital platforms is a result of the Internet development. Reading comprehension and audience skills are undoubtedly impacted by this, particularly for Generation Z because of shifting preferences for news-based-content consumption. By comparing Generation Z's preferences for classical and digital news sources, this study aims to comprehend the trends of news consumption in the digital age. This study used a quantitative approach using a descriptive methodology by employing a valid and reliable questionnaire to collect data that were then randomly distributed to 85 communication science students in semesters 2, 4, 6, and 8. The study's findings explain why communication science students do not vary significantly from other Generation Z students in terms of their preferences for news sources or how they consume them. However, since they study communication science, they are more astute when consuming news from contemporary sources that often include false information or aren't grounded in reality.